Continuous, Free‐Formable Sandwich Design with 3D Fiber Reinforced Core for Increased Lightweight Level of Applications in Large‐Scale Production. Issue 4 (25th July 2018) - Schäfer, Kay; Stiller, Jonas; Tröltzsch, Jürgen; Nestler, Daisy; Kroll, Lothar
Abstract : The object in this research is the development of a hybrid sandwich structure, which can be produced in large scale and substitute metals to reduce the weight of moving parts. The development uses a generic demonstrator in a complex shape. The innovative sandwich core consists of spacer fabric reinforced polyurethane flexible foam. The facings are thermoplastic composites. An additional spacer fabric linked to the outside of one facing serves as an extra feature like silencer, filter, or human‐machine‐interface. The large‐scale production of such complex structures according to the current state of the art is challenging and shall be realized in this topic in an injection molding environment. The realization of the process needs several differential examinations of the individual lightweight materials and process steps, which are presented in this paper. Abstract : The development of continuous processes for the production of highly complex components consisting of fiber reinforced plastics (FRP) promises resource savings, energy efficiency, and high productivity. Against this background, the scientific work of this paper is carried out using a technology demonstrator in sandwich construction consisting of FRPs.